Effect of essential oil and supercritical carbon dioxide extract from the root of Angelica gigas on human EEG activity. (August 2017) - Sowndhararajan, Kandhasamy; Seo, Min; Kim, Minju; Kim, Heeyeon; Kim, Songmun
Abstract: Objectives: The present study aimed to investigate the effect of inhalation of essential oil (EO) and supercritical carbon dioxide extract (SC-CO2 ) from the root of A. gigas on human electroencephalographic (EEG) activity. Materials and methods: For this purpose, the EO was obtained from the root of A. gigas by steam distillation and SC-CO2 was obtained at 50 °C and 400 bar for 1 h. The EEG readings were recorded using the QEEG-8 system from 8 electrode sites according to the International 10-20 system. Results: In the EEG study, the absolute low beta (left temporal and left parietal) activity significantly increased during the inhalation of EO. In the case of SC-CO2 inhalation, there was no significant change in absolute waves. Conclusion: The results revealed that the EO of A. gigas root produced significant changes in the absolute low beta activity and these changes may enhance the language learning abilities of human brain. Highlights: The root part of Angelica gigas has been used in Korean traditional medicine. Effect of essential oil and SC-CO2 of A. gigas root on EEG activity was studied. The absolute low beta activity significantly increased during the inhalation of EO. There was no significant change in absolute waves during the inhalation of SC-CO2 . The inhalation of EO may enhance the language learning abilities of human.